Knowledge of Improved Cultivation Practices of Rose Grown by the Farmers of Khamnor Panchayat Samiti District of Rajsamand, Rajasthan - Rajesh Kumar Meena, M.S. Chauhan, B. Upadhyay (Indian Journal of Extension Education, 2022)
Rose is most important cut-flower. It occupies thefirst position in the foreign trade of cut-flower followedby Chrysanthemum and carnation. More than 140countries are involved in the world floriculture trade.Netherland is the largest producer as well as the exporterof the cut-flowers (63 per cent) in the world. Germany,on the other hand is the largest importer. Its share in theworld import has been around 37 per cent.